Analisis Kedalaman Dermaga Menggunakan Sistem Batimetri Untuk Pemetaan Dasar Laut di PT PAL Surabaya - Rizkiyono, Rico Andhika; Pratomo, Sunu Arsy; Wa' addulloh, Mu’izzaddin; Diansisti, Anisa; Hidayati, Ratna (Fakultas Teknik Universitas Maritim AMNI Semarang, 2025)
In an era of increasingly advanced technology, seabed mapping is very important in various fields, such as ship navigation, underwater infrastructure development, and marine environmental research. The use of a seabed sounding system at PT PAL has improved the quality of seabed mapping. The purpose of this study is to analyze the seabed at the PT PAL Surabaya pier in order to find out through seabed mapping using a bathymetric survey system and to find out the level of shallowing at each pier and which area is safe for ships to dock. This study uses a quantitative descriptive method. Pier sounding data using an echosounder tool at the PT. PAL Surabaya pier. The sounding data obtained starting from 2023 contains information about the depth of the pier, and will later be used to calculate Tool Correction, Fluctuation Correction, LWS (Low Water Spring) Correction, and Real Depth (actual depth). The results of the study show that based on the results of a bathymetric survey at PT. PAL in September 2023, the depth data at the West Peninsula pier is at a shallowest depth of 4 meters and the deepest is 6 meters. While the shallowest depth at the West Bandar pier is 3 meters and the deepest is 6 meters. At the North Peninsula pier the deepest depth is 8 meters marked with a solid green color. From these results it can be seen what ships can enter each particular pier area, namely ships that have a minimum draft of 2.65 m.